Rate of Force Development as an Indicator of Neuromuscular Fatigue: A Scoping Review - D’Emanuele, Samuel; Maffiuletti, Nicola A.; Tarperi, Cantor; Rainoldi, Alberto; Schena, Federico; Boccia, Gennaro (Frontiers in Human Neuroscience, 2021)
Because rate of force development (RFD) is an emerging outcome measure for the assessment of neuromuscular function in unfatigued conditions, and it represents a valid alternative/complement to the classical evaluation of pure maximal strength, this scoping review aimed to map the available evidence regarding RFD as an indicator of neuromuscular fatigue. Thus, following a general overview of the main studies published on this topic, we arbitrarily compared the amount of neuromuscular fatigue between the “gold standard” measure (maximal voluntary force, MVF) and peak, early (≤ 100 ms) and late (> 100 ms) RFD. Seventy full-text articles were included in the review. The most-common fatiguing exercises were resistance exercises (37% of the studies), endurance exercises/locomotor activities (23%), isokinetic contractions (17%) and simulated/real sport situations (13%). The most widely-tested tasks were knee extension (60%) and plantar flexion (10%). The reason (i.e., rationale) for evaluating RFD was lacking in 36% of the studies. On average, the amount of fatigue for MVF (-19%) was comparable to late RFD (-19%) but lower compared to both peak RFD (-25%) and early RFD (-23%). Even if the rationale for evaluating RFD in the fatigued state was often lacking and the specificity between test task and fatiguing exercise characteristics was not always respected in the included studies, RFD seems to be a valid indicator of neuromuscular fatigue. Based on our arbitrary analyses, peak RFD and early phase RFD appear even to be more sensitive to quantify neuromuscular fatigue than MVF and late phase RFD.